The non-deferrable mise-en-crise of the quotidian / O improrrogável colocar-em-crise do cotidiano - Rebolledo-Palazuelos, Felix (Revista Polis e Psique, 2017)
Abstract The perpetual crisis of Late Capitalism, ubiquitously present in our quotidian as background to all being-doing, is confronted by the non-method of the mise-en-crise of our devising. By putting our quotidian in crisis, we educe crisis from the future and invoke the infinite potential of the anarchive—a drawing forth which produces chaos within process so that difference inhabits repetition. We rely on the active forgetting of inherited disciplined knowledges and perfected operating procedures to actualise modes and practices of composition which enable experimentation through a multiplicity of contemplations and aberrant becomings. We espouse an affirmative, immanent critique as a mode of knowing and composing so that when we ask “What next?” we leave no other course of action other than the ineluctable exercise of our subjectivity as the facticity of resolution of crisis. Keywords: Crisis; Anarchive; Critique; Quotidian; Non-deferral. Resumo A crise perpétua do capitalismo tardio, presente de forma ubíqua em nosso cotidiano como pano de fundo de todo ser-fazendo, é confrontada com o não-método da mise-en-crise de nossa concepção. Colocando nosso cotidiano em crise, geramos crise do futuro e invocamos o potencial infinito do anarquivo - um desdobramento que produz o caos dentro do processo para que a diferença habite a repetição. Contamos com o esquecimento ativo de conhecimentos disciplinados herdados e procedimentos operacionais aperfeiçoados para atualizar modos e práticas de composição que permitem a experimentação através de uma multiplicidade de contemplações e de devires aberrantes. Adotamos uma crítica afirmativa e imanente como um modo de conhecer e compor, de modo que quando perguntamos "O que vem depois?", não deixamos outro curso de ação além do exercício inelutável de nossa subjetividade como facticidade de resolução de crises. Palavras-chave: Crise; Anarquivo; Crítica; Cotidiano; Improrrogável.